The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.4049/jimmunol.172.11.7192
|View full text |Cite
|
Sign up to set email alerts
|

A Promoter Haplotype of the Immunoreceptor Tyrosine-Based Inhibitory Motif-Bearing FcγRIIb Alters Receptor Expression and Associates with Autoimmunity. II. Differential Binding of GATA4 and Yin-Yang1 Transcription Factors and Correlated Receptor Expression and Function

Abstract: The immunoreceptor tyrosine-based inhibitory motif-containing FcγRIIb modulates immune function on multiple cell types including B cells, monocytes/macrophages, and dendritic cells. The promoter for the human FCGR2B is polymorphic, and the less frequent 2B.4 promoter haplotype is associated with the autoimmune phenotype of systemic lupus erythematosus. In the present study, we demonstrate that the 2B.4 promoter haplotype of FCGR2B has increased binding capacity for GATA4 and Yin-Yang1 (YY1) transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 43 publications
6
70
0
Order By: Relevance
“…Donors with the 2B.4 haplotype have increased mAb 4F5 staining on CD14 ϩ monocytes compared with 2B.1 homozygous donors (Fig. 7A, p Ͻ 0.002, twotailed, Mann-Whitney U test), which is in agreement with the previously reported expression of Fc␥RIIb in monocytes by Western blot analysis (21). Similarly, donors with the 2B.4 haplotype have increased 4F5 staining levels on neutrophils and CD19 Ϫ BDCA1 ϩ mDCs (Fig.…”
Section: The Expression Of Fc␥riib Is Regulated By Its Promoter Haplosupporting
confidence: 90%
See 3 more Smart Citations
“…Donors with the 2B.4 haplotype have increased mAb 4F5 staining on CD14 ϩ monocytes compared with 2B.1 homozygous donors (Fig. 7A, p Ͻ 0.002, twotailed, Mann-Whitney U test), which is in agreement with the previously reported expression of Fc␥RIIb in monocytes by Western blot analysis (21). Similarly, donors with the 2B.4 haplotype have increased 4F5 staining levels on neutrophils and CD19 Ϫ BDCA1 ϩ mDCs (Fig.…”
Section: The Expression Of Fc␥riib Is Regulated By Its Promoter Haplosupporting
confidence: 90%
“…Polymorphisms in the human FCGR2B gene are associated with the SLE phenotype (21)(22)(23)(24)(25)(26). We have recently demonstrated that polymorphisms in the regulatory region of FCGR2B form two major haplotypes and that the less frequent 2B.4 haplotype is significantly overrepresented in SLE patients (22).…”
Section: T He Only Inhibitory Igg Fcr In the Classical Fcr Family (1mentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16] For example, YY1 can enhance FCGR2B promoter activity by a functional promoter haplotype, which is also associated with SLE. 17 A genome-wide expression analysis revealed that YY1 may have a key role in the pathogenesis of multiple sclerosis or its subtypes. 18 In our study, we also showed that YY1 could have a role in transcription of WDFY4, with different affinity for a functional variant in the gene.…”
Section: Discussionmentioning
confidence: 99%